Analysis of Message Design Logics in the Debate Speeches of a Female Candidate in the 2024 East Java Gubernatorial Election - Novianty, Suci Marini; Mujiarto, Calysta Amelia (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2026)
This study aims to analyse the message design logics in the debate speeches of Luluk Nur Hamidah in the 2024 East Java Gubernatorial Election using O’Keefe’s Message Design Logic (MDL) framework. The study adopts a post-positivist approach with a qualitative content analysis method, focusing on messages as the unit of micro-level analysis. The research subject consists of the opening and closing speeches delivered by Luluk Nur Hamidah in the first, second, and third official gubernatorial debates. The data were obtained through speech transcription and segmented into 87 message units, which were subsequently coded into three MDL categories: Expressive, Conventional, and Rhetorical logics. The coding process was conducted systematically, and intercoder reliability was tested using Holsti’s formula. The findings indicate that Conventional Logic is the most dominant, followed by Expressive and Rhetorical logics. These results reflect a tendency toward message construction aligned with norms of politeness and communicative conventions in formal debate settings, accompanied by the articulation of social facts and programmatic statements. This study confirms the relevance of MDL as an analytical framework for mapping patterns of message design logics in political debate speeches at the textual level.